Simulation and practical implementation of a SEIG used in wind energy systems with rectified output voltage - Elshaibani, Duaa; Greibea, Sara; Alakeili, Loubna; Hammoda, Ahmed; Tahir, Ahmed; Khalil, Ashraf F.; Hassan, Zakariya; Khan, Sheroz; Ahmed, Syed Faiz; Ali, Athar (Institute of Electrical and Electronics Engineers Inc., 2018)
—The escalating energy demand worldwide coupled with the continues development in power electronics over the past few decades has led to an increasing interest in sustainable energy. Wind energy is considered as one of the most promising sources of renewable energy. In this paper, a self-excited induction generator is used to convert kinetic energy derived from the prime mover (wind turbine) into electrical energy. In order to supply the reactive power required by the machine, a three-phase capacitor bank is connected to the generator terminals. A three phase rectifier is used to utilize the conversion of the AC voltage and current at the generator terminals to DC voltage and current. Analytical model of the generator/rectifier system is derived and then simulated using MatLab/Simulink software. The results of the simulation are compared to practical implementation of the system which show a reasonable agreement.